Boron, aluminum, nitrogen, oxygen impurities in silicon carbide - Vlaskina, S.I.; Vlaskin, V.I.; Podlasov, S.A.; Rodionov, V.E.; Svechnikov, G.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
Diffusion of boron, aluminum, and oxygen was conducted at temperatures
1600 – 1700°C. Very pure original n-SiC crystal (6H-SiC) specially grown by the Lely
method annealed in oxygen during 2 h at 1700 °C, in argon during 2 h at 1700 °C, with
aluminum and silicon oxide powder during 2 h, and with boron oxide and aluminum
during 0.5 h. Electrical characterization of the silicon carbide samples was done by the
Hall effect measurements using the square van der Pauw method to determine the sheet
resistance, mobility, and free carrier concentration. The model of deep donor level as a
complex of nitrogen atom replacing carbon with adjacent silicon vacancy is suggested.